Determinan Pemilihan Karir Menjadi Akuntan Publik - Anandita Zulia Putri; Dwi Wastuti; Zidni Husnia Fachrunnisa (PRIVE: Jurnal Riset Akuntansi dan Keuangan, 2023)
The purpose of this study is to see how financial rewards/salaries, professional training, social values, work environment, and labor market considerations affect the choice of a career as a public accountant. Purposive sampling was used as a sample in this study. 52 auditors from the Yogyakarta Special Region Public Accounting Firm were used in this study. The analysis of this research uses the linear regression analysis technique. The findings of this study show how social values, work environment, professional training, financial rewards/salaries, and labor market factors influence the decision to pursue a career as a public accountant.